2018
DOI: 10.1186/s40723-018-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between structural factors and interaction quality in Norwegian ECEC for toddlers

Abstract: Background As a part of its welfare system, Norway provides universal access to early childhood education and care (ECEC) for all children between the ages of 1 and 5. To provide this access, Norway has undergone considerable structural changes in recent decades (Vassenden et al. 2011). These changes began with the 2003 ECEC settlement, which required municipalities to offer all children a place in ECEC. In 2009, access to a place in an ECEC programme became a legal right for all children. The overall purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…The analysis of the 14 articles selected for this review sheds light on aspects related to a positive classroom climate that can be categorized as "static" aspects, such as grouping, materials or decorative elements, or "dynamic" aspects, such as time or the quality of instruction, teacher-children interactions, and relationships with family members. These aspects can be grouped under the two dimensions that have been agreed upon in the literature to define quality in early childhood education: "structural aspects" and "pedagogical practices" (Andrews et al 2014;Barros et al 2016;Løkken et al 2018;Mathers et al 2014). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the 14 articles selected for this review sheds light on aspects related to a positive classroom climate that can be categorized as "static" aspects, such as grouping, materials or decorative elements, or "dynamic" aspects, such as time or the quality of instruction, teacher-children interactions, and relationships with family members. These aspects can be grouped under the two dimensions that have been agreed upon in the literature to define quality in early childhood education: "structural aspects" and "pedagogical practices" (Andrews et al 2014;Barros et al 2016;Løkken et al 2018;Mathers et al 2014). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some scholars (Loizou and Recchia, 2018 [36]) note that although infant education and care demands specific knowledge of infant development to better support their attempts to explore and communicate, teacher training is usually more focused on older children. In addition, teacher training commonly focuses on operational aspects such as preparing materials and planning activities, rather than on relationships or scaffolding (Barros et al, 2018 [37]; Chazan-Cohen et al, 2017 [38]; Gibbons, Stratford and White, 2017 [39]).…”
Section: The Specific Developmental Needs Of Infantsmentioning
confidence: 99%
“…Overall, the latter studies suggest that specialised training in working with infants and toddlers is critical to high process quality. The studies also stress the need for more research on the content of educators' preservice courses to better understand relationships between process quality and educators' formal education (Eckhardt and Egert, 2018 [4]; Loizou and Recchia, 2018 [36]; Schaack, Le and Setodji, 2017 [86]). For instance, in one study conducted in Germany, the authors found that playgroups with teachers who receive specific pre-service training in the area of early education and care (Pädagogische Fachschule) had higher levels of process quality compared to playgroups where teachers received other kind of training, but clearly more research is needed (Eckhardt and Egert, 2018 [108]).…”
Section: Higher Qualifications Are Associated With Higher Process Quamentioning
confidence: 99%
See 2 more Smart Citations